Namibia OH landscape: Challenges, opportunities and collaborative strategies - Angombe, Simon; Gorejena, Brighton; Freeman, Rachel J.; Kashona, Hainushka D.; Knight-Jones, Theodore J.D.; Caron, Alexandre; Hausiku, M.; Mwanyengange, I.; Richards, Shauna; Shivolo-Useb, S. (CAB International, 2024)
The Capacitating One Health in Eastern and Southern Africa (COHESA) initiative fosters research and innovation that facilitates seamless integration, customization, and operationalization of One Health (OH)-focused solutions. It is spearheaded by three consortia, namely, the International Livestock Research Institute (ILRI), Centre de coopération Internationale en recherche agronomique pour le développement (CIRAD), and the International Service for the Acquisition of Agri-biotech Applications (ISAAA). COHESA has 12 multipliers, including Namibia. Although Namibia does not currently have a formal OH Institute, key stakeholders recognize the importance of this concept. A baseline key informant survey conducted by Namibia’s project team revealed that participants acknowledged the significance of OH, particularly considering emerging and re-emerging diseases that affect humans, animals, plants, environmental health, and ecosystems. The cabinet’s recent approval of the Namibia Public Health Institute (NamPHI) is expected to enhance Namibia’s responses to public health threats. The National Action Plan on Health Security (NAPHS) of 2020 has facilitated a collaborative agreement between crucial line ministries (Ministry of Health and Social Services (MoHSS), the Ministry of Environment, Forestry and Tourism (MEFT), and the Ministry of Agriculture, Water and Land Reform (MAWLR)). However, the OH concept remains fragmented in private and government sectors. While the government emphasizes regulatory compliance, broad collaborations across sectors, and disease-centric initiatives, the private sector focuses more on industry-specific regulations, projects, and evaluations. Efforts should be made to bridge these gaps and foster more collaborative and coordinated approaches to address health challenges across Namibia’s multisectoral landscape.